2022
DOI: 10.1186/s12864-022-08549-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing, knockout and over-expression of a transcription factor ABORTED MICROSPORES (SlAMS) strongly affects pollen viability in tomato (Solanum lycopersicum)

Abstract: Background The tomato (Solanum lycopersicum L.) is an economically valuable crop grown worldwide. Because the use of sterile males reduces the cost of F1 seed production, the innovation of male sterility is of great significance for tomato breeding. The ABORTED MICROSPORES gene (AMS), which encodes for a basic helix-loop-helix (bHLH) transcription factor, has been previously indicated as an essential gene for tapetum development in Arabidopsis and rice. To determine the function of the SlAMS ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…These preliminary findings may help us better understand the impact of these mutations on the gene's ability to combat banana bunchy top disease. However, it is vital to underline the importance of additional functional studies such as gene silencing, knockout, and overexpression (Bao et al 2022) to further support and validate this inference.…”
Section: Discussionmentioning
confidence: 99%
“…These preliminary findings may help us better understand the impact of these mutations on the gene's ability to combat banana bunchy top disease. However, it is vital to underline the importance of additional functional studies such as gene silencing, knockout, and overexpression (Bao et al 2022) to further support and validate this inference.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study using AMS, another gene encoding a basic helix-loop-helix (bHLH) TF was knocked out by CRISPR/Cas9 and over-expressed in tomato. SlAMS downregulation or upregulation led to abnormal pollen development, which in turn decreased pollen viability, and subsequently generated male-sterile lines [5]. In our laboratory, we have generated completely male-sterile lines by mutating the SlPHD_MS1 gene (Solyc04g008420), encoding a PHD-type transcription factor [20].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, pollen development at tetrad, post-meiotic and mature stages were investigated in different tissues, including microspores, generative cells, pollen cells, callus, fully expanded leaves, pistil, and mature pollen grain (Figure S6). SlACO genes, four genes related to male sterility; SlPHD_MS1 [20], SlMS10 [21], SlAMS [5], SlSTR1 [22], and these 25 genes were hierarchically clustered by Manhattan distance in three anatomical parts including microspores, generative cell and pollen cell (Figure S6). Three sub-clusters were observed, and the SlACO2 gene was found to cluster separately from SlACO1.…”
Section: In-silico Functional and Expressional Characterization Of To...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Solyc01g081100 gene is a homolog of the Arabidopsis bHLH10/89/90 gene that, together with DYT1‐MYB35, forms a regulatory module during tapetum and pollen development (Cui et al., 2016 ). Recently, an ABORTED MICROSPORES ( AMS ) tomato homolog was identified that is essential for pollen development in this species (Bao et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%